Oral and maxillofacial surgery in dogs and cats - Verstraete, Frank J. M.; Lommer, Milinda J.; Bezuidenhout, A. J. (Abraham Johannes), 1942-; ScienceDirect eBooks (Edinburgh ; New York : Saunders/Elsevier, 2012)
Oral and Maxillofacial Surgery in Dogs and Cats offers a unique, detailed, comprehensive and highly illustrated account of surgical procedures that will improve outcomes for all surgical and dental specialists. In drawing together the expertise of specialists worldwide, it will also prove indispensable for general practitioners with a dental and oral caseload. Basic principles are considered prior to in-depth treatment of surgical conditions. The book combines expertise from both human and veterinary oral surgeons to provide an authoritative reference with a strongly practical slant. It is likely to become the standard work in the field for many years. Authoritative: over 30 international contributors who between them represent the peak of professional expertise in the field. Unique: the only book available devoted to a surgical specialty of growing relevance. Practical: profuse illustrations of the highest quality combine with step-by-step textual guidance to give clearest possible practical instruction. Detailed: presents in-depth descriptions of surgical conditions and detailed surgical explanations.
Nonsteroidal antiinflammatory drugs (NSAIDs)Carprofen; Ketorolac; Ketoprofen; Etodolac; Meloxicam; Deracoxib; Firocoxib; Tepoxalin; Balanced analgesia; References; Chapter 5 Enteral nutritional support; Therapeutic decision-making; Rationale for enteral nutritional support; Patient selection for nutritional support; Enteral feeding access devices; Nasoesophageal tubes; Pharyngostomy tubes; Esophagostomy tubes; Technique using curved Rochester-Carmalt, Mixter, or Schnidt forceps; Percutaneous feeding tube applicator technique; Percutaneous needle catheter technique; Complications.
Includes bibliographical references and index.
Title from publisher's Web site; (ScienceDirect, viewed on Aug. 7, 2012).
Elsevier
Keywords: Dogs -- Surgery; Cats -- Surgery; Mouth -- Surgery; Face -- Surgery; Dog Diseases -- surgery; Oral Surgical Procedures -- veterinary; Cat Diseases -- surgery; Maxillofacial Injuries -- veterinary; Mouth Diseases -- veterinary; MEDICAL -- Veterinary Medicine -- General; Cats -- Surgery; Dogs -- Surgery; Face -- Surgery; Mouth -- Surgery; Electronic books